Method for catalytically decomposing oxalic acid in nitric acid
By using the M-Si composite oxide support to support the active components of noble metals in the nitric acid solution, the problem of low efficiency of catalytic decomposition of oxalic acid in the prior art is solved, efficient decomposition of oxalic acid and the stability of the catalyst are achieved, and the plutonium recovery rate in the plutonium purification cycle is improved.
Patent Information
- Application Number
- CN202411834555.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art has low efficiency in catalytic decomposition of oxalic acid in nitric acid, and insufficient research on the design and performance of the catalyst, making it difficult to achieve efficient decomposition of oxalic acid under mild conditions.
A new catalyst is prepared by carrying the active components of precious metals using M-Si composite oxide support, which can efficiently decompose oxalic acid in nitric acid solution under mild conditions.
The efficient decomposition of oxalic acid is achieved, the decomposition conversion rate of oxalic acid in batch reaction reaches more than 99%, the catalyst properties are stable, and the service life is extended.
Smart Images

Figure BDA0005186722470000101 
Figure BDA0005186722470000111
Abstract
Description
Technical Field
[0001] The present application relates to a method for catalytically decomposing oxalic acid in nitric acid, belonging to the field of chemistry and chemical engineering. Background Art
[0002] The PUREX process is the mainstream process for commercial nuclear fuel reprocessing. After uranium and plutonium are co-decontaminated and separated, they enter the uranium purification process and the plutonium purification process respectively. In plutonium purification, oxalic acid is usually added as a precipitant to precipitate it. The mother liquor after filtering the plutonium oxalate precipitate is called the plutonium oxalate precipitation mother liquor. The plutonium concentration in the mother liquor is about 10-100 mg / L, and the oxalic acid concentration is about 0.1 mol / L. In order to recover the plutonium in the plutonium oxalate precipitation mother liquor, it needs to be returned to the plutonium purification cycle in the PUREX process for extraction. The small amount of oxalic acid contained in the mother liquor has a strong complexing ability for plutonium, which will reduce the distribution coefficient of plutonium.
[0003] This will affect the plutonium recovery rate in the plutonium purification cycle and may also cause precipitation, which will also affect the extraction equipment.
[0004] In order to ensure the normal operation of the equipment, the concentration of oxalate introduced must be strictly controlled. Generally, the return oxalate
[0005] The destruction rate of oxalic acid in plutonium mother liquor reaches over 99%. Therefore, the destruction of oxalic acid is particularly important for achieving the plutonium purification cycle in the PUREX process.
[0006] my country's post-processing plants use KMnO4 cooking to destroy oxalic acid in the mother liquor. Although this method is simple to operate and has a short reaction time, the amount of oxalic acid in the waste liquid is proportional to the amount of potassium permanganate. Adding too much oxalic acid will cause K + and Mn 2+ It accumulates in the process flow, thus complicating the final disposal of the waste liquid. In order to solve this problem, researchers at home and abroad have conducted in-depth research, and the methods reported include: direct destruction by chemical reagents (ozone oxidation, hydrogen peroxide oxidation), electrolytic destruction, photodecomposition, etc. Although the above methods can destroy oxalic acid to a certain extent, they have the problem of low efficiency. In addition to the above methods, catalytic oxidation of oxalic acid with nitric acid is also a research direction. This method can be divided into heterogeneous catalysis and homogeneous catalysis. Heterogeneous catalysis generally uses platinum-loaded catalysts, and homogeneous catalysis uses vanadium ions and manganese ions as catalysts. Among them, the research on Mn(Ⅱ) is the most mature, and industrial applications have been achieved abroad.
[0007] The use of heterogeneous catalysts to decompose oxalic acid has the characteristics of fast and stable reaction and no induction period. At the same time, the catalyst is recyclable and does not introduce impurity ions. It is currently considered to be one of the preferred methods to replace the KMnO4 cooking method. Krot et al. proposed the use of Pt / SiO catalyst and BAU activated carbon to decompose hydrazine and oxalic acid in nitric acid solution. The experiment found that when hydrazine was completely decomposed, oxalic acid began to decompose.
[0008] in the presence of hydrazine in nitric acid solutions in solid-phase catalysts, Radiokhimiya, 1995, 37 (1), 23-27). Tyumentsev et al. studied the performance of Pt-Ru bimetallic catalysts supported on silicon oxide in the catalytic decomposition reaction of oxalic acid and found that the catalyst containing 80 at.% Pt had the highest activity. All bimetallic catalysts could accelerate the reaction, and the catalyst prepared by co-deposition method had the strongest activity (Synergistic effect inheterogeneously catalyzed reduction of U(VI) and Np(V) and decomposition of hydrazine and oxalic acid with bimetallic Pt-Ru catalysts, Physical Chemistry, 2013, Vol. 450, Part 2, pp. 142-145). Hao Shuai et al. studied the reaction mechanism of Pt / SiO catalytic decomposition of oxalic acid: the degradation process of oxalic acid in nitric acid solution occurred on the catalyst surface, NO3 - Adsorbed on the active site and reacted with Pt on the catalyst surface to generate oxidized intermediates Pt-O, H + To promote this reaction, the oxalic acid molecules degrade with Pt-O through oxidative dehydrogenation reaction to generate OOC-COOH that is easily self-decomposed, and finally produce CO2 (Catalytic reactions of oxalic acid degradation with Pt / SiO2 as a catalyst in nitric acid solutions, RSC Advances, 2023, 13, 22758-22768).
[0009] The above reports only focus on the study of reaction kinetics and reaction mechanism, while there are almost no reports on the design and performance of catalysts in the decomposition of oxalic acid. By optimizing the design of catalysts and thus improving the activity of catalysts, it is expected to achieve efficient decomposition of oxalic acid under mild conditions. Summary of the invention
[0010] The present invention aims to solve three technical problems. The first problem is the catalyst problem for catalytic decomposition of oxalic acid in nitric acid solution. A new catalyst is provided, which can achieve efficient decomposition of oxalic acid under mild conditions. The second problem is the preparation method of the catalyst for solving the above problem one. The method uses an M-Si composite oxide carrier to load a noble metal active component, which can effectively enhance the interaction between the carrier and the active component. The third problem is to use the catalyst to achieve catalytic decomposition of oxalic acid in nitric acid solution.
[0011] According to one aspect of the present application, a method for catalytically decomposing oxalic acid in nitric acid is provided, comprising the following steps:
[0012] The nitric acid solution containing oxalic acid is contacted with a catalyst to react and remove the oxalic acid therein;
[0013] In the nitric acid solution containing oxalic acid, the concentration of nitric acid is 0.5-5 mol / L, and the concentration of oxalic acid is 0.5-4 mol / L;
[0014] The catalyst is composed of a composite carrier and an active metal element loaded on the surface of the composite carrier;
[0015] The composite carrier is composed of metal oxide and silicon dioxide;
[0016] The metal oxide is selected from at least one of aluminum oxide, titanium oxide, zirconium oxide and cerium oxide;
[0017] The active metal element is selected from at least one of Pt, Ru, Pd, Ir and Rh;
[0018] In the catalyst, the mass fraction of active metal elements is 0.01-10wt%, the mass fraction of silicon dioxide is 0.01-20wt%, and the rest is metal oxide.
[0019] The catalyst is obtained by the following steps:
[0020] The composite carrier is immersed in an aqueous solution containing an active metal precursor, dried, calcined, and reduced with hydrogen to obtain the catalyst.
[0021] The active metal precursor is selected from at least one of nitrates or chlorides of Pt, Ru, Pd, Ir and Rh.
[0022] The immersion temperature is 25-30°C;
[0023] The immersion time is 1 to 24 hours;
[0024] The drying temperature is 60-120°C;
[0025] The drying time is 8 to 24 hours;
[0026] The calcination temperature is 300-500°C;
[0027] The calcination time is 6 to 12 hours;
[0028] The temperature of the hydrogen reduction is 200-600°C;
[0029] The pressure of the hydrogen reduction is normal pressure;
[0030] The hydrogen reduction time is 3 to 24 hours;
[0031] The gas flow rate of the hydrogen reduction is 50 to 500 h -1 ;
[0032] The heating rate of the hydrogen reduction is 5-10°C / min.
[0033] The composite carrier is obtained by the following steps:
[0034] The metal oxide, solvent and cationic surfactant are mixed, and then ammonia water and soluble silicon source are added, heat-treated, filtered, washed, dried and calcined to obtain the composite carrier.
[0035] The solvent is selected from water and / or ethanol;
[0036] The cationic surfactant is selected from at least one of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride;
[0037] The soluble silicon source is selected from at least one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and butyl orthosilicate.
[0038] The temperature of the heat treatment is 20 to 60°C;
[0039] The heat treatment time is 4 to 24 hours;
[0040] The drying temperature is 60-120°C;
[0041] The drying time is 1 to 2 hours;
[0042] The calcination temperature is 400-600°C;
[0043] The calcination time is 4 to 12 hours.
[0044] The reaction temperature is 30-90°C;
[0045] The reaction pressure is normal pressure.
[0046] The beneficial effects of this application include:
[0047] (1) The catalyst of the present invention has stable properties, which is beneficial to prolonging the service life of the catalyst.
[0048] (2) The catalyst of the present invention can efficiently decompose oxalic acid in nitric acid solution. In an intermittent reaction, the decomposition conversion rate of oxalic acid reaches more than 99% within 25 minutes. DETAILED DESCRIPTION
[0049] The technical details of the present invention are described in detail by the following examples. It should be noted that the examples are only used to further illustrate the technical features of the present invention, rather than to limit the present invention.
[0050] Example 1
[0051] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.25g of hexadecyltrimethylammonium bromide, stir evenly, add 7.50g of ammonia water and 1.95g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 25°C for 12h, filter, wash 3 times with deionized water, dry at 80°C for 12h, and calcine at 500°C for 4h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-10Si.
[0052] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-10Si composite carrier, soak at room temperature for 24h, dry at 120℃ for 8h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Al-10Si.
[0053] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0054] Example 2
[0055] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.1g of dodecyldimethylbenzylammonium chloride, stir evenly, add 7.50g of ammonia water and 1.41g of methyl orthosilicate dropwise into the mixture solution, stir at 40°C for 6h, filter, wash 3 times with deionized water, dry at 80°C for 12h, and calcine at 400°C for 8h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-10Si.
[0056] Weigh 0.10g PdCl2 and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-10Si composite carrier, soak at room temperature for 16h, dry at 100℃ for 16h, and calcine at 300℃ for 8h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 300℃, H2 space velocity: 50h -1 , reduction time: 4h, the catalyst is recorded as: 3Pd-Al-10Si.
[0057] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0058] Example 3
[0059] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.15g of hexadecyltrimethylammonium chloride, stir evenly, add 7.50g of ammonia water and 2.44g of propyl orthosilicate dropwise to the mixture solution, stir at 60°C for 10h, filter, wash 3 times with deionized water, dry at 120°C for 6h, and calcine at 400°C for 8h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-10Si.
[0060] Weigh 0.155g RuCl33 H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-10Si composite carrier, soak at room temperature for 24h, dry at 120℃ for 24h, and calcine at 300℃ for 12h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 300h -1 , reduction time: 6h, the catalyst is recorded as: 3Ru-Al-10Si.
[0061] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0062] Example 4
[0063] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.20g of octadecyltrimethylammonium chloride, stir evenly, add 7.50g of ammonia water and 2.96g of butyl orthosilicate dropwise into the mixture solution, stir at 30°C for 24h, filter, wash 3 times with deionized water, dry at 120°C for 2h, and calcine at 600°C for 12h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-10Si.
[0064] Weigh 0.122g RhCl3 and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-10Si composite carrier, soak at room temperature for 24h, dry at 120℃ for 12h, and calcine at 500℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 500℃, H2 space velocity: 500h -1 , reduction time: 3h, the catalyst is recorded as: 3Rh-Al-10Si.
[0065] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0066] Example 5
[0067] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.25g of hexadecyltrimethylammonium bromide, stir evenly, add 7.50g of ammonia water and 1.95g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 25°C for 12h, filter, wash 3 times with deionized water, dry at 80°C for 12h, and calcine at 500°C for 4h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-10Si.
[0068] Weigh 0.127g H2IrCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-10Si composite carrier, soak at room temperature for 24h, dry at 120℃ for 12h, and calcine at 300℃ for 12h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 200℃, H2 space velocity: 400h -1 , reduction time: 6h, the catalyst is recorded as: 3Ir-Al-10Si.
[0069] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0070] Example 6
[0071] Weigh 5.00g of titanium oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.25g of hexadecyltrimethylammonium bromide, stir evenly, add 7.50g of ammonia water and 1.95g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 60°C for 12h, filter, wash 3 times with deionized water, dry at 80°C for 12h, and calcine at 600°C for 8h to obtain a TiO2-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Ti-10Si.
[0072] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.0ml deionized water to prepare a mixed solution, pour it into 1.94g Ti-10Si composite carrier, soak at room temperature for 24h, dry at 120℃ for 24h, and calcine at 400℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Ti-10Si.
[0073] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0074] Example 7
[0075] Weigh 5.00g of zirconium oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.25g of hexadecyltrimethylammonium bromide, stir evenly, add 7.50g of ammonia water and 1.95g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 25°C for 12h, filter, wash with deionized water 3 times, dry at 120°C for 12h, and calcine at 400°C for 8h to obtain a ZrO2-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Zr-10Si.
[0076] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.8ml deionized water to prepare a mixed solution, pour it into 1.94g Zr-10Si composite carrier, soak at room temperature for 6h, dry at 120℃ for 8h, and calcine at 500℃ for 12h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 300℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Zr-10Si.
[0077] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration: 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 60°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0078] Example 8
[0079] Weigh 5.00g of cerium oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.25g of hexadecyltrimethylammonium bromide, stir evenly, add 7.50g of ammonia water and 1.95g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 60°C for 24h, filter, wash with deionized water 3 times, dry at 120°C for 1h, and calcine at 500°C for 8h to obtain a CeO2-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Ce-10Si.
[0080] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.5ml deionized water to prepare a mixed solution, pour it into 1.94g Ce-10Si composite carrier, soak at room temperature for 6h, dry at 120℃ for 10h, and calcine at 400℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 300℃, H2 space velocity: 500h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Ce-10Si.
[0081] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 30°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0082] Example 9
[0083] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.25g of hexadecyltrimethylammonium bromide, stir evenly, add 7.50g of ammonia water and 1.95g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 25°C for 12h, filter, wash 3 times with deionized water, dry at 80°C for 12h, and calcine at 500°C for 4h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-10Si.
[0084] Weigh 0.005g H2PtCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-10Si composite carrier, soak at room temperature for 1h, dry at 120℃ for 10h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 200℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 0.1Pt-Al-10Si.
[0085] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration: 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0086] Example 10
[0087] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.25g of hexadecyltrimethylammonium bromide, stir evenly, add 7.50g of ammonia water and 1.95g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 25°C for 12h, filter, wash 3 times with deionized water, dry at 80°C for 12h, and calcine at 600°C for 4h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-10Si.
[0088] Weigh 0.531g H2PtCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-10Si composite carrier, soak at room temperature for 6h, dry at 120℃ for 10h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 600℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 10Pt-Al-10Si.
[0089] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0090] Embodiment 11
[0091] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.10g of hexadecyltrimethylammonium bromide, stir evenly, add 1.0g of ammonia water and 0.175g of tetraethyl orthosilicate dropwise to the mixture solution, stir at 40°C for 12h, filter, wash 3 times with deionized water, dry at 80°C for 12h, and calcine at 500°C for 4h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-0.1Si.
[0092] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-0.1Si composite carrier, soak at room temperature for 24h, dry at 120℃ for 10h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Al-0.1Si.
[0093] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0094] Example 12
[0095] Weigh 5.00g of aluminum oxide and disperse it in 60mL of deionized water and 60mL of anhydrous ethanol, add 0.10g of hexadecyltrimethylammonium bromide, stir evenly, add 7.5g of ammonia water and 4.33g of tetraethyl orthosilicate dropwise into the mixture solution, stir at 25°C for 12h, filter, wash 3 times with deionized water, dry at 60°C for 12h, and calcine at 500°C for 4h to obtain an Al2O3-Si composite carrier with a mass fraction of SiO2 of 10%, recorded as Al-20Si.
[0096] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g Al-20Si composite carrier, soak at room temperature for 24h, dry at 120℃ for 8h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Al-20Si.
[0097] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0098] Comparative Example 1
[0099] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g alumina carrier, soak at room temperature for 24h, dry at 120℃ for 8h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Al.
[0100] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0101] Comparative Example 2
[0102] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.0ml deionized water to prepare a mixed solution, pour it into 1.94g titanium oxide carrier, soak at room temperature for 24h, dry at 120℃ for 8h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Ti.
[0103] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 80°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0104] Comparative Example 3
[0105] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.5ml deionized water to prepare a mixed solution, pour it into 1.94g zirconium oxide carrier, soak at room temperature for 24h, dry at 120℃ for 8h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Zr.
[0106] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration: 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 60°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0107] Comparative Example 4
[0108] Weigh 0.1593g H2PtCl6·6H2O and dissolve it in 1.55ml deionized water to prepare a mixed solution, pour it into 1.94g cerium oxide carrier, soak at room temperature for 24h, dry at 120℃ for 8h, and calcine at 300℃ for 6h. The calcined catalyst is reduced in H2 atmosphere, reduction temperature: 400℃, H2 space velocity: 100h -1 , reduction time: 4h, the catalyst is recorded as: 3Pt-Ce.
[0109] The conditions for the catalyst to catalyze the decomposition of oxalic acid are: nitric acid concentration 4.0 mol / L, oxalic acid concentration: 0.35 mol / L, reaction temperature: 30°C, pressure: normal pressure. The reaction results are shown in Table 1.
[0110] Table 1 Performance of different catalysts in catalytic decomposition of oxalic acid in nitric acid solution
[0111]
[0112]
[0113] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A method for catalytically decomposing oxalic acid in nitric acid, characterized in that: The following steps are involved: The nitric acid solution containing oxalic acid is contacted with a catalyst to react and remove the oxalic acid therein; In the nitric acid solution containing oxalic acid, the concentration of nitric acid is 0.5-5 mol / L, and the concentration of oxalic acid is 0.5-4 mol / L; The catalyst is composed of a composite carrier and an active metal element loaded on the surface of the composite carrier; The composite carrier is composed of metal oxide and silicon dioxide; The metal oxide is selected from at least one of aluminum oxide, titanium oxide, zirconium oxide and cerium oxide; The active metal element is selected from at least one of Pt, Ru, Pd, Ir and Rh; In the catalyst, the mass fraction of active metal elements is 0.01-10wt%, the mass fraction of silicon dioxide is 0.01-20wt%, and the rest is metal oxide.
2. The method according to claim 1, characterized in that The catalyst is obtained by the following steps: The composite carrier is immersed in an aqueous solution containing an active metal precursor, dried, calcined, and reduced with hydrogen to obtain the catalyst.
3. The method according to claim 2, characterized in that: The active metal precursor is selected from at least one of nitrates or chlorides of Pt, Ru, Pd, Ir and Rh.
4. The method according to claim 2, characterized in that: The immersion temperature is 25-30°C; The immersion time is 1 to 24 hours; The drying temperature is 60-120°C; The drying time is 8 to 24 hours; The calcination temperature is 300-500°C; The calcination time is 6 to 12 hours; The temperature of the hydrogen reduction is 200-600°C; The pressure of the hydrogen reduction is normal pressure; The hydrogen reduction time is 3 to 24 hours; The gas flow rate of the hydrogen reduction is 50 to 500 h -1 ; The heating rate of the hydrogen reduction is 5-10°C / min.
5. The method according to claim 2, characterized in that: The composite carrier is obtained by the following steps: The metal oxide, solvent and cationic surfactant are mixed, and then ammonia water and soluble silicon source are added, heat-treated, filtered, washed, dried and calcined to obtain the composite carrier.
6. The method according to claim 5, characterized in that The solvent is selected from water and / or ethanol; The cationic surfactant is selected from at least one of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride; The soluble silicon source is selected from at least one of methyl orthosilicate, ethyl orthosilicate, propyl orthosilicate and butyl orthosilicate.
7. The method according to claim 5, characterized in that The temperature of the heat treatment is 20 to 60°C; The heat treatment time is 4 to 24 hours; The drying temperature is 60-120°C; The drying time is 1 to 2 hours; The calcination temperature is 400-600°C; The calcination time is 4 to 12 hours.
8. The method according to claim 1, characterized in that The reaction temperature is 30-90°C; The reaction pressure is normal pressure.